International Lateinamerika-Kolloquium 2009 - abstracts and program - Wörner, Gerhard; Möller-McNett, Stefan (Universitätsverlag Göttingen, 2009)
The International Lateinamerika-Kolloquium, held in April 2009 at the Geosciences Centre of the Georg-August-Universität Göttingen, brings together researchers from all fields of earth sciences. The abstracts contained in this volume cover a wide range of topics on the geological evolution of the South American continent and its margins, such as processes of mountain building, uplift and erosion as well as interaction between tectonic and climatic parameters. Topics of the Lateinamerika-Kolloquium also cover landscape evolution, ecology, natural resources, geo-hazards and economic geology.